Climatology and interannual variability of type-dependent aerosol optical depth and vertical distribution over southwest China and northern India from multiple satellite and aerosol reanalysis datasets. (1st February 2023) - Cai, Hongke; Gui, Ke; Jiang, Wanting; Mao, Yaqin; Yang, Yue; Zhao, Zuosen
Abstract: Aerosol loading and properties have an important influence on the radiative effect of aerosols and regional climate change. Based on the long-term datasets of aerosol optical products retrieved from multiple satellite observations (MODIS/Terra, MODIS/Aqua, MISR, and CALIOP/CALIPSO) and a reanalysis product (CAMS) from 2007 to 2019, the climatology and interannual variability in total aerosol optical depth (AOD) and type-dependent AODs related to aerosol particle properties and components over southwest China (SWC) and northern India (NI) are investigated, and the vertical distribution of type-dependent aerosol extinctions are also examined. Overall, consistent spatial distribution characteristics of the AOD climatology are captured across the different datasets, albeit with slight differences in magnitude. Multi-year mean high AODs are mainly concentrated in areas such as the Sichuan Basin (SCB) (∼0.5) and NI (∼0.6), dominated by anthropogenic aerosols, and the Tarim Basin (∼0.5), dominated by mineral dust aerosols. In contrast, the central Tibetan Plateau (CTP) area, with a relatively clean background, has a lower AOD (∼0.1) on a multi-year average basis. When the total AOD is separated by chemical components, the CAMS reanalysis demonstrates that sulfate and carbonaceous aerosols (CAs) contribute nearly equally to AOD in SCB, while CAs is the largest contributor to the high aerosol loading in NI. An enhanced vertical aerosol extinction coefficient (AEC) is mainly located below 1 km in both SCB and NI, reaching 0.35 km −1 and 0.55 km −1 . In CTP, the AEC has two peaks (∼0.02 km −1 ) at 2.5 km and 3.5 km. By partitioning the column AOD by different altitude ranges, we find that about 73.8% (80.6%) of the AOD in SCB (NI) is located in the lower troposphere (0–2 km). The resulting trend analyses show that a significant decreasing (increasing) trend ( P  < 0.05) in AOD in SCB (NI) is accurately captured by both the satellite products and the CAMS reanalysis. In contrast, a significant decline ( P  < 0.1) in the CTP region is observed in CAMS only, while a non-significant decline is detected in the satellite products. The results of this study have potential implications for understanding the vertical distribution and interannual variability of regional aerosol loading. Highlights: Climatology of type-dependent AODs over SWC and NI were presented. Sulfate and CAs contribute nearly equally to AOD in SCB. CAs is the largest contributor to the high aerosol loading in NI. About 73.8% (80.6%) of the AOD in SCB (NI) is located within 0–2 km. A significant decreasing (increasing) AOD trend in SCB (NI) is captured.